AKIBAT HUKUM DARI CACAT TERSEMBUNYI PADA BARANG DALAM KEGIATAN TRANSAKSI BARANG BEKAS - Aryawan Saddewa, I Made; Adiyaryani, Ni Nengah (Kertha Semaya : Journal Ilmu Hukum, 2015)
This writing shall be entitled as “Law Impact Of Hidden Defect In SaleTransaction Of Things In Used Condition”. This writing shall apply the normativeanalysis method combined with statutory approach, in Indonesia thats so many peoplehave do many ways to get incrase of their lives, one of them is do the economic activityis sale transaction of things in used condition to get the profit, however in saletransaction of things in used condition. This paper also raised the issue that the purposeof writing is about the law impact a rising from hidden defect of things as well as thesetting in conducting the sale of used things. Through the preparation of this paper byusing normative analysis method or approach to legislation, then reaching a conclusionthat the law impact of hidden defects in transaction of things in used condition foundin article 1504 Code Civil Code as well as the code in transaction of used things inarticle 1 paragraph 3, article 8 paragraph 2, and article 62 paragraph 1 of Lawnumber 8 of 1999 on Consumer Protection.
Keywords: Law Impact, Hidden Defect, Transaction, Used Things